GAME EDUCATIONAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES (ResearchJet Journal of Analysis and Inventions, 2021)
The article is devoted to game educational technologies and their application in foreign language lessons. The article reveals the functions and value of game forms of learning in the educational process of a foreign language. Special attention is paid to the classification of language and speech games. Based on the analysis of existing classifications, the authors propose their own classification, focusing on creative and role-playing games in foreign language lessons.